A1.03 Arginase I and osteoclastogenesis. (24th February 2016) - Brunner, JS; Hofmann, M; Saferding, V; Paar, H; Chen, L; Cheng, P; Schabbauer, G; Blüml, S
Abstract : Background and objectives: Osteoclasts are giant, multi-nucleated cells that derive from the monocyte-macrophage linage and are involved in bone turnover. They are further known as the main effector cells for development of age-related osteoporosis. While the role of Arginase I within certain myeloid lineages such as macrophages is well appreciated, its role within osteoclasts is relatively unknown. Our aim was therefore to investigate the importance of the enzyme in the context of osteoclastogenesis. Materials and methods: We analysed osteoclastogenesis of C57BL/6J or BALB/c wildtype cells in vitro in the presence and absence of recombinant Arginase I (recARG1) and its inhibitor nor-NOHA. This was complemented via qPCR analysis of marker genes. We further investigated the potential of the enzyme to induce cell death via flow cytometry analysis of 7-AAD and Annexin V. Results: In osteoclast differentiation assays, we show that Arginase I is strongly downregulated during osteoclastogenesis, suggesting involvement of this enzyme in OC differentiation. We further show that addition of recArgI completely abolishes osteoclast formation without inducing cell death. The inhibitory effect of recArgI on osteoclastogenesis was completely dependent on the enzymatic function, as no decrease in osteoclast formation could be observed during combined addition of recArgI and its specific inhibitor nor-NOHA. We further demonstrate that recArgI specifically inhibits RANKL-mediated terminal differentiation of OCs, but has no effect on MCSF dependent generation of OC precursors. In line, we could show that addition of recombinant Arginase I negatively regulated the expression of classic RANKL induced osteoclastic marker genes such as TRAP and Cathepsin K. Conclusions: We propose that recArgI might be a potent inhibitor of osteoclastogenesis and could prove itself to be useful for the treatment of osteoclast driven diseases, such as osteoporosis.